Prognostic Value of the CLIF‐C AD Score in Patients With Implantation of Transjugular Intrahepatic Portosystemic Shunt. Issue 4 (5th January 2021) - Sturm, Lukas; Praktiknjo, Michael; Bettinger, Dominik; Huber, Jan P.; Volkwein, Lara; Schmidt, Arthur; Kaeser, Rafael; Chang, Johannes; Jansen, Christian; Meyer, Carsten; Thomas, Daniel; Thimme, Robert; et al.
Abstract : Prognostic assessment of patients with liver cirrhosis allocated for implantation of a transjugular intrahepatic portosystemic shunt (TIPS) is a challenging task in clinical practice. The aim of our study was to assess the prognostic value of the CLIF‐C AD (Acute Decompensation) score in patients with TIPS implantation. Transplant‐free survival (TFS) and 3‐month mortality were reviewed in 880 patients who received de novo TIPS implantation for the treatment of cirrhotic portal hypertension. The prognostic value of the CLIF‐C AD score was compared with the Model for End‐Stage Liver Disease (MELD) score, Child‐Pugh score, and albumin‐bilirubin (ALBI) score using Harrell's C concordance index. The median TFS after TIPS implantation was 40.0 (34.6‐45.4) months. The CLIF‐C AD score (c = 0.635 [0.609‐0.661]) was superior in the prediction of TFS in comparison to MELD score (c = 0.597 [0.570‐0.623], P  = 0.006), Child‐Pugh score (c = 0.579 [0.552‐0.606], P  < 0.001), and ALBI score (c = 0.573 [0.545‐0.600], P  < 0.001). However, the CLIF‐C AD score did not perform significantly better than the MELD‐Na score (c = 0.626 [0.599‐0.653], P  = 0.442). There were no profound differences in the scores' ranking with respect to indication for TIPS implantation, stent type, or underlying liver disease. Subgroup analyses revealed that a CLIF‐C AD score >45 was a predictor of 3‐month mortality in the supposed low‐risk group of patients with a MELD score ≤12 (14.7% vs. 5.1%, P  < 0.001). Conclusion: The CLIF‐C AD score is suitable for prognostic assessment of patients with cirrhotic portal hypertension receiving TIPS implantation. In the prediction of TFS, the CLIF‐C AD score is superior to MELD score, Child‐Pugh score, and ALBI score but not the MELD‐Na score. Abstract : In the present study we investigated the value of the CLIF‐C AD score for prognostic assessment of patients with liver cirrhosis allocated for implantation of a transjugular intrahepatic portosystemic shunt (TIPS) for the treatment of portal hypertension. Indeed, the CLIF‐C AD score performed significantly better in the prediction of transplant‐free survival following TIPS implantation in comparison to the MELD score ( P  = 0.008), the Child Pugh score ( P  < 0.001) and the ALBI score ( P  < 0.001). However, the CLIF‐C AD score performed only marginally better than the MELD‐Na score ( P  = 0.442).